Suppressing ion migration of CsPbBrxI3-x nanocrystals by Nickel doping and the application in high-efficiency WLEDs. (24th May 2021) - Yang, Supeng; Zhu, Hanwen; Xu, Enze; Li, Junchun; Yang, Heming; Zhang, Yan; Zhu, Zhifeng; Jiang, Yang
Abstract: All inorganic perovskite nanocrystals CsPbX3 (X = Cl, Br, I) are the great potential candidates for the application of high-performance light emitting diodes (LED) due to their high Photoluminescence Quantum Yield (PLQY), high defect tolerance, narrow full-width half-maximum and tunable wavelength of 410–700 nm. However, the application of red-emitting (630–650 nm) CsPbBr x I3- x nanocrystals are perplexed by phase segregation due to the composition of mixed halides and the difference in halide ion mobility. Herein, we provide an effective strategy to suppressing the migration of Br/I ions through Ni 2+ doping via a facile Hot-Injection method and the PLQY was improved as well. DFT calculations show that the introduction of Ni 2+ causes a slight contraction of the host crystal structure, which improves the bond energy between Pb and halides and reduces the level of surface defects. Therefore, the phase stability is improved by Ni 2+ doping because the phase segregation caused by ion migration in the mixed phase is effectively inhibited. Meanwhile, the non-radiative recombination in the exciton transition process is reduced and the PLQY is improved. What's more, benefiting from the suppressed ion migration and enhanced PLQY, we combine the Ni 2+ -doped CsPbBr x I3- x nanocrystals with different Br/I ratios and YAG: Ce 3+ phosphors as color conversion layers to fabricate high efficiency WLED. When the ratio of Br/I is 9:11, WLED has a color coordinate of (0.3621, 0.3458), the color temperature of 4336 K and presents a high luminous efficiency of 113.20 lm W −1, color rendering index of 94.9 under the driving current of 20 mA and exhibits excellent stability, which shows great potential in the application of LED.